Reactualiting Phanera semibifida (Roxb.) Benth. from Sumatra, Indonesia as an Anticancer Agent and Phylogenetic Position - f, Fitmawati; Juliantari, Erwina; Roza, Rodesia Mustika; t, Titrawani; Yahya, Vanda Julita (Pharmacognosy Reviews)
The increasing prevalence of cancer worldwide demands the intensification of efforts to develop natural solutions for its treatment. Herbal plants have provided a strong evident base in treating of this disease in many indigenous tribes in the world. Phanera semibifida has been widely used as a viable anti-degenerative drug for cancer treatment. This study reviews selected plant species with taxonomy status, phylogeny position, phytochemistry and pharmacology study based on a author’s research and literature review conducted through relevant keyword searches in databases, Web of Science, Scopus, PubMed, and Google Scholar. Detailed analysis of research studies proves that P. semibfida can be used as an anticancer agent with strong basic evidence based on indigenous knowledge from traditional communities.
Keywords: Anticancer; Leguminosae; Phanera semibifida; Pharmacology; Sumatra